Management Strategies for Endometriosis in Women: Literature Review - Ermiati, Ermiati; Alfiah, Umi; Islamey, Rasyadan Savero; Rahmawati, Rika (Universitas Prima Indonesia, 2026)
Endometriosis is a chronic, estrogen-dependent gynecological disorder affecting women of reproductive age and is associated with persistent pain, organ dysfunction, and infertility. Despite the availability of various treatment options, its management remains challenging due to complex pathophysiology and variable responses to therapy. This literature review aims to summarize recent evidence on management strategies for endometriosis and to highlight their clinical implications. A descriptive literature review was conducted using a systematic search of four databases which are PubMed, Scopus, EBSCOhost, and ScienceDirect for articles published between 2020 and 2025. Following the PRISMA 2020 guidelines, an initial search identified 45,014 records. After screening titles and abstracts and assessing full-text eligibility, six primary studies met the inclusion criteria and were included in the final synthesis. The included studies were analyzed thematically and categorized into five main therapeutic approaches: hormonal therapy, immunological therapy, antioxidant therapy, surgical therapy, and traditional or complementary therapy. Overall, these strategies demonstrated potential benefits in reducing pain, improving fertility-related outcomes, and lowering postoperative recurrence when applied in appropriate clinical contexts. Rather than indicating a single optimal treatment, the findings emphasize the importance of individualized and multimodal management tailored to symptom severity, reproductive goals, and treatment tolerance. This review contributes to the existing literature by integrating diverse and emerging management strategies into a cohesive framework that supports clinical decision-making. Clinically, the findings underscore the value of patient-centered care, careful monitoring of treatment effects, and interdisciplinary collaboration, including psychosocial support, to optimize long-term outcomes for women with endometriosis.